Guidelines for Purchasing and Using Commercial Natural Enemies and Biopesticides in North America - Lynn M. LeBeck; Norman C. Leppla (EDIS)
This guide provides assistance in selecting, purchasing, and using commercially available natural enemies and biopesticides for managing pest problems. The guide assists in the identification of pests by habitat and lists types of natural enemies (parasitic nematodes, predatory mites, predatory insects, and parasitic wasps) and biopesticides available to manage these pests. Scientific and product names are provided both for insect and mite natural enemies and for some of the most common microbial insecticides, nematicides, and fungicides that can be used to manage pests. Biological control companies are listed along with their websites, and the guide provides additional sources of information on obtaining and using commercial natural enemies. Written by Lynn M. LeBeck and Norman C. Leppla, and published by the UF Department of Entomology and Nematology, August 2015.